A One Health approach to address the productivity of emerging smallholder cattle farming: a system dynamics application in the highveld region of South Africa - Van Heerden, Nicolette (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.